Women as foreign policy leaders national security and gender politics in superpower America - Bashevkin, Sylvia B. (Oxford studies in gender and international relations, 2018)
This book is a comparative examination of women's presence in senior national security positions in the United States executive branch. It looks at four appointees in the United States since 1980: Jeane Kirkpatrick during the Reagan years, Madeleine Albright in the Clinton era, Condoleezza Rice during the George W. Bush presidency, and Hillary Rodham Clinton in the first Obama mandate. It explores the extent to which each of these women was able to fully participate in a domain long dominated by men, focusing in particular on the extent to which each shaped foreign policy in meaningful ways. The author looks particularly at two specific phenomena: first, the influence of female decision-makers,notably their ability to make measurable difference to the understanding and practice of national security policy; and second, leaders' actions with respect to matters of war and women's rights. The track records of these four women reveal not just a consistent willingness to pursue muscular,aggressive approaches to international relations, but also widely divergent views about feminism.